Ancillary Services via Flexible Photovoltaic/Wind Systems and "Implicit" Storage to Balance Demand and Supply. Issue 8 (29th September 2022) - Pierro, Marco; Barba, Mario; Perez, Richard; Perez, Marc; Moser, David; Cornaro, Cristina
Abstract : Achieving the European Union renewable energy source penetration 2030 targets requires an increase in flexible resources to compensate for the variability/intermittency of solar and wind generation to ensure system safety and balancing. Herein, two readily deployable flexibility solutions to balance demand/supply as an alternative to building additional thermoelectric reserves are proposed. How the transmission system OPERATOR can use the ancillary services provided by a flexible photovoltaic (PV) fleet (solar regulation) or PV/wind fleet (variable renewable energy (VRE) regulation) together with a suitable underforecast and proactive curtailment of variable renewable generation (aka, implicit storage) to reduce current and future Italian imbalances is shown. How these flexibility solutions can become even more effective when combined with a strengthening of the transmission grid is shown. The imbalance reduction achievable by 2030 through solar/VRE regulation strategies would be of the order of 20–50% with zonal balancing and 27–80% with nationwide balancing is found. Imbalance costs would remain comparable with the business‐as‐usual (thermal generation) costs. A proactive curtailment of 5–17% of the total VRE generation is the environmental cost of stabilizing the system using VRE plants, avoiding the construction of thermoelectric reserves. Abstract : A variable renewable energy fleet, once equipped with storage, smart inverters, and power plant controllers (flex variable renewable energy systems), can be managed by the transmission system operator as the thermoelectric secondary reserve. A flexible photovoltaic fleet could provide the ancillary services required to resolve the daylight imbalance between residual demand and scheduled supply.